Progress of Selected Projects During the Second Five Year Plan - Planning Commission, Government of India (Planning Commission, Government of India, 1961)
The report on “Progress on Selected Projects During the Second Five-Year Plan” provides a comprehensive overview of India’s strategic initiatives across multiple sectors between 1956 and 1961, highlighting infrastructure and industrial development aimed at accelerating economic growth. Key projects included multipurpose river valley initiatives such as the Bhakra Nangal, Damodar Valley, Hirakud, Kosi, and Chambal projects, which focused on irrigation, flood control, and hydroelectric power, generating substantial employment and enhancing agricultural productivity. Industrial expansions were emphasized through steel production plants at Rourkela, Bhilai, Durgapur, and Tata Iron and Steel Company, alongside fertilizer manufacturing facilities like Rourkela, Nangal, Sindri, and Travancore, aiming to strengthen self-sufficiency and chemical production capabilities. Infrastructure and technology advancements included railway electrification, the Ganga Bridge project, and investments in shipbuilding and telecommunications via Hindustan Shipyard Ltd. and Indian Telephone Industries Ltd., supported by foreign collaborations and technical training programs. The report underscores substantial financial commitments, both domestic and international, to enhance production capacities, operational efficiency, and human capital development. Collectively, these projects reflect the Second Five-Year Plan’s holistic approach to integrating water resources, energy, industry, and technology to lay a robust foundation for India’s economic modernization, with forward-looking projections extending into the Third Plan to further strengthen industrial and infrastructural resilience.
Government of India Planning Commission Statistics and Surveys Division New Delhi
Keywords: Second Five Year Plan; Bhakra Nangal Project; Rourkela Steel Plant; Fertilizer Production; Damodar Valley Corporation; Hirakud Dam; Industrial Development; Employment Generation; Irrigation and Power; Infrastructure Expansion